If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4y + 5(y + -2) = -16 + 10 Reorder the terms: -4y + 5(-2 + y) = -16 + 10 -4y + (-2 * 5 + y * 5) = -16 + 10 -4y + (-10 + 5y) = -16 + 10 Reorder the terms: -10 + -4y + 5y = -16 + 10 Combine like terms: -4y + 5y = 1y -10 + 1y = -16 + 10 Combine like terms: -16 + 10 = -6 -10 + 1y = -6 Solving -10 + 1y = -6 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + 1y = -6 + 10 Combine like terms: -10 + 10 = 0 0 + 1y = -6 + 10 1y = -6 + 10 Combine like terms: -6 + 10 = 4 1y = 4 Divide each side by '1'. y = 4 Simplifying y = 4
| 2/5x-2=4x-14 | | 2x+10=2x+6 | | 2(x-5)+6=7(x-1)-2(x-6) | | 4x*4x+19x+21=0 | | x^2+8x-105= | | 3x+12-6x=18-14x+11x-6 | | 10-(2y-5)=8-3y | | 3x^2+6x+10=y | | 62/-10 | | x*x+16x-4=9x+4 | | 5x-3(x-4)=-6+5x+12 | | 32-6y+7y=-15+28 | | x*x+11x+31=7 | | a^2+8a-33= | | 2cs-17=a | | y^2-2y-16x+49=0 | | 37/y*4/7=74/35 | | 2x-6/4+x+5/6 | | 4(c+4.3)=6(c+1.8) | | -1/2(x-6)=3x | | -6-9r=-10r | | a=p+rt | | x*x-6x-40=0 | | M/19-1=-2 | | 13x-7+3x-4=12x-3+3 | | 8(-6b+5)=328 | | 7(b-0.5)=2(b+4.5) | | s+5/2s+20=48 | | -6n+9=-9n | | 8y-4y=-2 | | x-4/4+2=5 | | 2xz-4-z=4 |